2012
DOI: 10.1167/iovs.11-8409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lamina Cribrosa and Peripapillary Sclera Stiffness in Pseudoexfoliation and Normal Eyes by Atomic Force Microscopy

Abstract: AFM was proven suitable for determining the stiffness of ONH tissues, encouraging further large-scale analyses. The marked decrease in stiffness, implying an increased deformability of the ONH in PEX eyes, may reflect an inherent tissue weakness rendering these eyes more vulnerable to glaucomatous damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 52 publications
1
68
1
1
Order By: Relevance
“…Follow up biological experiments suggests that the protective effect may be a consequence of stabilization of the ECM due to increased elastin and fibrillin-1 deposition. This notion is supported by histopathological observations demonstrating decreased elastic fiber formation and tissue stiffness as well as impaired cell adhesion in ocular tissues of patients with XFS 60,61 . We speculate that carrying the rare protective p.407Tyr variant could maintain cellular integrity and render cells more resistant to environmental stressors which destabilize or disrupt the ECM.…”
Section: Discussionmentioning
confidence: 54%
“…Follow up biological experiments suggests that the protective effect may be a consequence of stabilization of the ECM due to increased elastin and fibrillin-1 deposition. This notion is supported by histopathological observations demonstrating decreased elastic fiber formation and tissue stiffness as well as impaired cell adhesion in ocular tissues of patients with XFS 60,61 . We speculate that carrying the rare protective p.407Tyr variant could maintain cellular integrity and render cells more resistant to environmental stressors which destabilize or disrupt the ECM.…”
Section: Discussionmentioning
confidence: 54%
“…For older PXS patients, OCT measurements of peripapillary retinal thickness should be performed frequently in order to monitor RNFL loss and to ensure timely intervention for early treatment of visual function damage. The decreased stiffness of the lamina cribrosa and peripapillary scleral tissues caused by PXS may reflect an inherent tissue weakness, especially in older patients [37,38] . This may in turn render these eyes more vulnerable to IOP fluctuations and optic nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that a marked decrease in stiffness of the LC in PXS eyes would result in increased deformability of the ONH in these patients. 11 Peripheral deformation in the LC structure, either in PXS or in NTG patients, may lead to increased susceptibility of retinal ganglion cell (RGC) axons to pressure-induced damage, thus making it a potential risk factor of glaucoma development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in PXS, a primary disturbance of the elastic fiber homeostasis in this structure may lead to decreased stiffness and increased deformability of the ONH, rendering PEX eyes more vulnerable to pressure-induced optic nerve damage and glaucoma development and progression. [9][10][11] The nutrition of the choroid could be another possible source of vulnerability of PXS eyes to develop glaucoma. As an analogy, some histologic studies have demonstrated decreased density of capillaries and large choroidal vessels as well as choroidal thinning in advanced primary angle closure glaucoma.…”
mentioning
confidence: 99%